Psammocoryza vanemdeni, a new genus and species of scaritine beetle from the Atlantic coast of Brazil (Coleoptera: Carabidae: Clivinini) - Hogan, James E. (Zootaxa, 2006)
A new genus of Clivinini, Psammocoryza Hogan new genus, and its type species P.vanemdeni Hogan new species (type locality Barra de Serinhaem, Pernambuco, Brazil), is described. Diagnostic features are illustrated by line drawings and photographs. Psammocoryza resembles Halocoryza Alluaud and Schizogenius Putzeys but differs by the peculiar macrosculpture of the pronotum, tuberculate profemora and reduced setation of the gonocoxite.